The Philosophy Of Knowledge And The Development Of Science And Technology As The Foundation Of Islamic Education - Herman Darmawan (Jurnal Ilmu Pendidikan Nasional (JIPNAS), 2024)
The question that is most often raised is how science can become the basis for every development of civilization. With this, civilization can be supported by every theory put forward systematically which is embedded in science, and all of this also has an impact on the development of science and technology. Therefore, this study tries to explore issues regarding the nature of science and the development of science and technology along with their influence on contemporary developments under the pretext of being able to restore understanding of science and the development of science and technology. This science is divided into several discussion sections, including nature, function, object, source, truth tester and classification. The development of science and technology includes understanding, influence, ethical responsibility for the use of technology and its influence on Islamic education and how Islamic education responds to developments in science and technology